2022
DOI: 10.1038/s41598-022-10600-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial links between subchondral bone architectural features and cartilage degeneration in osteoarthritic joints

Abstract: Early diagnosis of osteoarthritis (OA), before the onset of irreversible changes is crucial for understanding the disease process and identifying potential disease-modifying treatments from the earliest stage. OA is a whole joint disease and affects both cartilage and the underlying subchondral bone. However, spatial relationships between cartilage lesion severity (CLS) and microstructural changes in subchondral plate and trabecular bone remain elusive. Herein, we collected femoral heads from hip arthroplasty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Currently, subchondral bone deterioration is thought to precede the onset of cartilage damage 23,24 . Meanwhile, subchondral bone abnormal angiogenesis is observed in OA samples 11,25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, subchondral bone deterioration is thought to precede the onset of cartilage damage 23,24 . Meanwhile, subchondral bone abnormal angiogenesis is observed in OA samples 11,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, subchondral bone deterioration is thought to precede the onset of cartilage damage. 23 , 24 Meanwhile, subchondral bone abnormal angiogenesis is observed in OA samples. 11 , 25 Therefore, we collected tibial plateaus from two OA patients to investigate the underlying mechanisms regulating subchondral bone ECs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the corresponding changes such as reduction in subchondral plate mineralization density may indicate the early stages of OA, and we should pay attention to this in order to intervene early in the development of OA. 31 In addition, Zhen et al 32 found that increased TGFβ1 in subchondral bone can significantly increase subchondral bone volume and angiogenesis, significantly reduce proteoglycan expression, and thin the hyaline cartilage layer, thus inducing the joint to display OA phenotype, whereas inhibition of TGFβ activity in subchondral bone can inhibit OA progression. In the joint region, there are many potential instances of molecular crosstalk within and between tissues.…”
Section: The Key Role Of Subchondral Bony Zone In Oamentioning
confidence: 99%
“…It has been reported that there is a complex interaction between cartilage and subchondral bone. Many literatures show that that signi cant changes of subchondral bone remodeling occurred at the very early stage in a rat OA model, and alternations in subchondral bone emerged earlier than cartilage degeneration 8, 22,23 . Micro-CT scans revealed a signi cant increase in the number of trabeculae in the JTG group, which were well aligned, closely spaced, and signi cantly thicker.…”
Section: Protective Effect Of Jtgmentioning
confidence: 99%